Unveiling Intrinsic Value in Biodiversity Accounting: A Challenge for Accountants in Indonesia - Asni, Nur; Sawarjuwono, Tjiptohadi (Jurnal Dinamika Akuntansi dan Bisnis, 2020)
This study aims to develop a conceptual framework of biodiversity accounting within the frame of intrinsic value using a deep ecological concept approach. This approach views biodiversity has inherent value as an object in the environment. Despite the difficulty to measure the intrinsic value of biodiversity, several studies have developed and used different methods for assessing and unveiling biodiversity in the entitys reports. It has been a challenge for accounting science and the accounting profession in Indonesia to develop biodiversity accounting which can be incorporated into the entity's financial statements. Therefore a conceptual framework is needed to integrate the intrinsic value. The proposed conceptual framework is developed from the first level, which is the policy or regulation as the basis for planning ecological activities. It is followed by the second level, i.e. the implementation process in the form of specific projects. Finally, the third level is the evaluation of the performance of the entity's ecological activities (P3FEA).